Ecosystem response to climatic change: the importance of the cold season - Bokhorst, Stef; Bjerke, Jarle W; Tømmervik, Hans; Preece, Catherine; Phoenix, Gareth K (Ambio, 2012)
Winter climate and snow cover are the important drivers of plant community development in polar regions. However, the impacts of changing winter climate and associated changes in snow regime have received much less attention than changes during summer. Here, we synthesize the results from studies on the impacts of extreme winter weather events on polar heathland and lichen communities. Dwarf shrubs, mosses and soil arthropods were negatively impacted by extreme warming events while lichens showed variable responses to changes in extreme winter weather events. Snow mould formation underneath the snow may contribute to spatial heterogeneity in plant growth, arthropod communities and carbon cycling. Winter snow cover and depth will drive the reported impacts of winter climate change and add to spatial patterns in vegetation heterogeneity. The challenges ahead lie in obtaining better predictions on the snow patterns across the landscape and how these will be altered due to winter climate change.
Publisher: Springer Netherlands
Keywords: Antarktis; biologi; botanikk; dyr; klimaendringer; leddyr; planter; snø; sopper; zoologi; økosystemer

Mumifiserte seler fra Dronning Maud Land, Antarktis - Gjertz, Ian; Wiig, Øystein (Fauna, 2001)
Keywords: Dronning Maud Land; dyr; seler; zoologi